Metabolic and hormonal effects of 'catch‐up' sleep in men with chronic, repetitive, lifestyle‐driven sleep restriction. (6th March 2015) - Killick, Roo; Hoyos, Camilla M.; Melehan, Kerri L.; Dungan, George C.; Poh, Jonathon; Liu, Peter Y.
Summary Objective Acutely restricting sleep worsens insulin sensitivity in healthy individuals whose usual sleep is normal in duration and pattern. The effect of recovery or weekend 'catch‐up' sleep on insulin sensitivity and metabolically active hormones in individuals with chronic sleep restriction who regularly 'catch‐up' on sleep at weekends is as yet unstudied. Design 19 men (mean ± SEM age 28·6 ± 2·0 years, BMI 26·0 ± 0·8 kg/m2) with at least 6 months' history (5·1 ± 0·9 years) of lifestyle‐driven, restricted sleep during the working week (373 ± 6·6 min/night) with regular weekend 'catch‐up' sleep (weekend sleep extension 37·4 ± 2·3%) completed an in‐laboratory, randomized, crossover study comprising two of three conditions, stratified by age. Conditions were 3 weekend nights of 10 hours, 6 hours or 10 hours time‐in‐bed with slow wave sleep (SWS) suppression using targeted acoustic stimuli. Measurements Insulin sensitivity was measured in the morning following the 3rd intervention night by minimal modelling of 19 samples collected during a 2‐h oral glucose tolerance test. Glucose, insulin, c‐peptide, leptin, peptide YY (PYY), ghrelin, cortisol, testosterone and luteinizing hormone (LH) were measured from daily fasting blood samples; HOMA‐IR, HOMA‐β and QUICKI were calculated. Results Insulin sensitivity was higher following three nights of sleep extension compared to sustained sleep restriction. Fasting insulin, c‐peptide, HOMA‐IR, HOMA‐β, leptin and PYY decreased with 'catch‐up' sleep, QUICKI and testosterone increased, while morning cortisol and LH did not change. Targeted acoustic stimuli reduced SWS by 23%, but did not alter insulin sensitivity. Conclusions Three nights of 'catch‐up' sleep improved insulin sensitivity in men with chronic, repetitive sleep restriction. Methods to improve metabolic health by optimizing sleep are plausible.